Putusan Hakim pada Perkara No. 177/Pdt.G/2023/Pa.Kng Dan No. 763/Pdt.G/2023/Pa.Kng Tentang Sengketa Harta Bersama Hukum Islam Dan Hukum Positif - Lubis, Asmuliadi (El 'Ailaah, 2024)
Joint assets are assets acquired during marriage outside of gifts or inheritance. What this means is the assets obtained through the efforts of the husband and wife during the marriage before the divorce occurred. Based on the positive book that applies in Indonesia, joint property in marriage is contained in Law number 1 of 1974, whereas in Islamic law there are no regulations. The purpose of this research is to find out what the judge's decision was in joint property case No. 177/Pdt.G/2023/Pa.Kng and No. 763/Pdt.G/2023/PA.Kng, how Islamic law and positive law review the decision and to analyze the results of the comparison between Islamic law and positive law on the judge's decision in joint property case No. 177/Pdt.G/2023/Pa.Kng and No. 763/Pdt.G/2023/PA.Kng This research uses qualitative methods with a descriptive data collection approach. The type of research used is field research. The data sources used are primary and secondary data sources. The data collection techniques used were interviews and documentation. The research instruments used were interview guides and documentation formats. The data analysis technique used is qualitative data analysis. The data that the author obtained was then reduced, presented and concluded using comparative descriptive analysis techniques. The conclusion in this research is that based on the decision of the Panel of Judges it can be concluded that from the various considerations that have been made, in case No. 177/Pdt.G/2023/Pa.Kng The Hakım Council did not accept the joint property lawsuit because the lawsuit submitted could not be clearly proven regarding the status and specifications of the joint property. Meanwhile, in case No. 763/Pdt.G/2023/PA.Kng The Panel of Judges accepted the joint property lawsuit because each party had agreed to divide the joint property into two parts. Judging from Islamic law and positive law, sourced from the Al-Qur'an Surah Ah-Imran verse 159, Al-Maidah verse 1, Qaidah Fiqh "Harm must be eliminated" and the Civil Code, the decision not to accept joint property entitlement in the case No. 177/Pdt.G/2023/Pa.Kng and the decision to accept the joint property claim in case No. 763/Pdt.G/2023/PA.Kng is permitted because it is in accordance with Islamic law and positive law. Based on the comparison results, it can be concluded that the judge's decision regarding the joint property dispute in case No. 177/Pdt.G/2023/Pa.Kng and No. 763/Pdt.G/2023/PA.Kng both according to Islamic law and positive law, the decision of the Panel of Judges not to accept and accept the joint property claim is appropriate.